An Anlysis of Students' Ability in Identifying Pronouns in Senior High School Grade 10 of SMKN 1 Batusangkar - Rhadia Cheyri Assyfa; M. Zaim (Journal of English Language Teaching, 2023)
Some of the tenth-grade students at SMKN 1 Batusangkar have been taught about pronouns, but they still make mistakes when identifying them, according to preliminary research. As a result, the goals of this study were to find out how well students at SMKN 1 Batusangkar's tenth grade use pronouns and what kind of pronouns they have the most trouble recognizing. Quantitative research was used in this study. The tenth-grade students of the state SMKN 1 Batusangkar in the academic year 2021/2022 were the subject of this study, and the student's ability in identifying pronouns were the object of this study. The researcher chose 33 students from 324 students as the sample using the cluster sampling method. The researcher used a grammar test to gather the data. The researcher identified the kinds of pronouns that students made when identifying pronouns through data analysis. Students made the most mistakes with demonstrative pronouns (226 students, or 68.48 percent), interrogative pronouns (216 students, or 65.45 percent), reflexive pronouns (195 students, or 59.09 percent), possessive pronouns (190 students, or 58.48 percent), and personal pronouns (176 students, or 53.33 percent).